Quantitative X-ray phase-contrast digital histology of liver metastases in a mouse model - Lorenzo Massimi; Sara Vitale; Laura Maugeri; Luca Businaro; Giuseppe Gigli; Micol E. Fiori; Alessia Cedola (Scientific Reports)
Abstract Investigating the tissue modifications occurring as a consequence of tumour development is an important goal in preclinical medical research, as it can provide a better understanding of the mechanisms behind its origin and spread. Tumor microenvironment has a supportive role in cancer development and can be exploited as a therapeutic target to prevent and contrast metastatic spread, which usually leads to a poor prognosis. In this work, a colorectal cancer model of liver metastasis is used to perform proof-of-concept quantitative investigations of the changes occurring in murine liver tissue due to the formation of metastases. X-ray phase contrast imaging performed with synchrotron radiation was used to obtain high resolution and contrast on soft tissues with minimum sample preparation and a large field of view on a 3D volume. A pixel size of 3 µm, and 0.7 µm have been used. to visualize and quantify liver microvasculature, referred to as sinusoids, and to identify significant morphological differences between control and metastatic tissues. A reorganization of the hepatic tissue, characterized by increased vascularization around the metastatic lesions coupled with a significant reduction in the sinusoidal network in the distal liver parenchyma was observed. X-ray findings are also supported by conventional histology, proving X-ray phase contrast imaging as an informative complementary technique.